Midwifery Care for Postpartum Mothers With After Pain Discomfort in Maternity Homes and Clinics: Asuhan Kebidanan pada Ibu Nifas Dengan Ketidaknyamanan After Pain di Rumah Bersalin dan Klinik - Hafifa, Hafifa; Hanum, Sri Mukhodim Faridah; Rosyidah, Rafhani (Indonesian Journal of Innovation Studies, 2020)
The postpartum period is an important period for health workers to monitor the mother's condition. The coverage of postpartum mothers' visits in 2016 was 71.54%. target coverage of postpartum mother visits in 2017 with the aim of transferring knowledge and complete postpartum visits. This type of method uses a descriptive method. whose main purpose is to make an objective picture of a situation.